Pengaruh Profitabilitas, Leverage, dan Size Perusahaan terhadap Return Saham Sektor Consumer Non-Cyclical - Cahyani, Bintang Defri; Imronudin, Imronudin (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the impact of profibality,firm size, and leverage on stock returns in companies within the non-cyclical consumer sector listed on the Indonesia stock exchange. Research methodology: This studi employs a purposive sampling technique, selecting companies that meet specific criteria to examine the relationship between the independent and dependent variabel Results: The research results show that profitability, leverage and company size have a significant effect on stock returns. Profitability and leverage show a positive influence, indicating that companies with higher profitability and leverage tend to provide better stock returns. In addition, larger company size is also associated with increased stock returns. Conclusions: Profitability, leverage, and firm size have a significant impact on stock returns. Additionally, collectively, profitability, leverage, and firm size have been proven to have a significant effect on stock returns. This demonstrates that these three factors collectively play an important role in determining stock returns across various industries and essential goods sectors. Limitations: This study utilizes data from companies in the non-cyclical consumer sector listed on the Indonesia stock exchange Contribution: These findings are expected to serve as valuable insights for investors when making investment decisions in the non-cyclical cosumer sector.